Visual Revolutions in the Middle East. Issue 3 (26th May 2016) - Westmoreland, Mark R.; Allan, Diana K.
Abstract : Five years ago images from the Arab uprisings revealed a renewed investment in political visibility. Despite the brutal outcome of most of these revolts, the centrality of seeing for understanding the dynamics of political vision and struggle in the region remains salient. Images serve as important touchstones around which political narratives emerge and cohere. In this special issue on Visual Revolutions in the Middle East, seven scholars— Diana K. Allan, Zeynep Devrim Gürsel, Alisa Lebow, Peter Limbrick, Anjali Nath, Peter Snowdon and Mark R. Westmoreland—bring interdisciplinary attention to the generative possibilities of image-making in sites of political contestation. Whether through archival remnants, mobile screen technologies or the lens of a camera, the contributors to this collection explore the image as an agent of expression, engagement and critique, operating at the interface between political desires and evidentiary forms of visuality.